Monitoring residual 36 h post-match neuromuscular fatigue in rugby union; a role for postural control?. Issue 10 (26th November 2019) - Troester, Jordan C.; Duffield, Rob
Abstract: The present study investigated single-leg balance and landing measures, respectively, at the beginning of a weekly micro-cycle 36 h after a match compared to 48 h rest without any match load. Twenty-seven professional rugby union players performed balance and landing tests on a 1000 Hz force plate across three in-season micro-cycles either with or without match loads in the prior 36 h. Participants were further sub-divided into higher and lower match load groups to investigate changes in balance and landing variables. Differences between rested and 36 h post-match single-leg balance sway velocity were trivial in all cases, except for the higher-load group on the dominant leg, which were possibly impaired 36 h post-match (ES ± 90% CL = 0.68 ± 0.66). Differences between rested and 36 h post-match single-leg landing measures of relative impulse on the non-dominant leg were possibly lower (0.36 ± 0.34), with possible impairment observed on both legs in the higher load group 36 h post-match (0.39 ± 0.33; 0.49 ± 0.42). Differences in landing measures of peak force and time to stabilisation were mainly trivial (ES < 0.20). Postural control measures at 36 h post-match are comparable to a rested state; though impairment of sway velocity on the dominant leg and landing impulse may indicate residual neuromuscular fatigue resulting from increased match exposure.